2008
DOI: 10.1063/1.2960339
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced current study of stacking faults and partial dislocations in 4H-SiC Schottky diode

Abstract: Electrical properties of stacking faults and bounding partial dislocations in 4H-SiC Schottky diode were investigated by using electron-beam-induced current ͑EBIC͒ and cathodoluminescence ͑CL͒ techniques. EBIC images show that basal plane dislocation is easily dissociated into two partial dislocations ͓Si ͑g͒ 30°and C ͑g͒ 30°partials͔, with a stacking fault between them. The EBIC contrast of C ͑g͒ 30°partial is always several percent higher than that of Si ͑g͒ 30°partial. The stacking fault is brighter than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…It has been found that stacking faults (SFs) are easily created and developed in 4H-SiC devices during forward-bias stressing 3,4 or electron-beam (e-beam) irradiation. [5][6][7] Formation and subsequent development of SFs in the active region of devices could be a reason for their degradation. 8,9 Therefore, the study of SFs has received considerable attention from both the applied and fundamental research communities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that stacking faults (SFs) are easily created and developed in 4H-SiC devices during forward-bias stressing 3,4 or electron-beam (e-beam) irradiation. [5][6][7] Formation and subsequent development of SFs in the active region of devices could be a reason for their degradation. 8,9 Therefore, the study of SFs has received considerable attention from both the applied and fundamental research communities.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic boundary condition is applied to the system simulated. In the defect structure proposed from the EBIC and CL experiments, 5,6) …”
Section: Methodsmentioning
confidence: 99%
“…4,5) Recently, Electron-beam-induced current (EBIC) and cathodoluminescence (CL) study on 4H-SiC have shown that BPDs are easily dissociated into two partial dislocations with a SF between them under the electron-beam irradiation. 6) In this paper, we report a study on the atomic-and electronic-structure of a dislocation loop and a stacking fault in 4H-SiC. We focus on the local atomic structure similar to that reported in the aforementioned experiment and investigate by using large-scale tight-binding (TB) moleculardynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Dislocation behavior has been extensively studied in Si-face 4H-SiC over a number of years [1][2][3][4][5][6][7][8]. It is known that basal plane dislocations (BPDs) show the highest recombination strength [3], and under forward bias stressing or electron-beam (ebeam) irradiation the BPDs can easily dissociate into partial dislocations with the formation of stacking faults (SFs) inside [1,4,5]. It is shown that C-core partial is immobile, while Si-core partial is mobile that causes the expansion of the SFs [9,10].…”
mentioning
confidence: 99%